Pengaruh Budaya Perusahaan Terhadap Produktivitas Karyawan Dimediasi Variabel Loyalitas Kerja di PT. Ochiai Menara Indonesia - Fahad Hisyam; Suhartini; Maulid, Muhammad Reza (Indonesian Journal of Innovation Science and Knowledge, 2025)
This study is motivated by the importance of corporate culture in creating a conducive work environment that enhances employee productivity. A strong corporate culture is believed to shape positive and productive attitudes, character, and work behaviors; however, these effects do not occur directly, but rather through employee loyalty. The purpose of this study is to analyze the influence of corporate culture on employee productivity with work loyalty as a mediating variable. This study employs a quantitative approach, utilizing a survey method among employees. Data was collected through the distribution of questionnaires. A total of approximately 100 employees participated and filled in this data, of course, to permanent employees of the company and analyzed using the Structural Equation Modeling (SEM) model with the help of SmartPLS software. The results of the study indicate that corporate culture has an indirect effect on employee productivity, but a significant positive impact on work loyalty. Furthermore, work loyalty has a significant positive effect on employee productivity. Additionally, it was found that work loyalty strongly mediates the relationship between corporate culture and productivity. These results emphasize the importance of strengthening organizational culture as a strategy for improving employee performance indirectly by increasing work loyalty. This finding highlights that building a strong work culture is insufficient for companies if it is not complemented by strategies that foster employee loyalty. Organizational culture must be translated into real practices, such as employee empowerment, two-way communication, and recognition of individual contributions. Training programs on cultural values, internal discussion forums, and a fair reward system are practical steps that need to be adopted. This study aims to analyze the effect of corporate culture on employee productivity with work loyalty as a mediating variable. This study was conducted at a manufacturing company. By understanding this relationship, it is hoped that the company can design a more effective workplace culture strategy to increase employee loyalty and productivity sustainably.